Consolidating the grain boundary of the garnet electrolyte LLZTO with Li3BO3 for high-performance LiNi0.8Co0.1Mn0.1O2/LiFePO4 hybrid solid batteries. Issue 36 (25th July 2019) - Xie, Huilin; Li, Chunli; Kan, Wang Hay; Avdeev, Maxim; Zhu, Chenyou; Zhao, Zhikun; Chu, Xiaorong; Mu, Daobin; Wu, Feng
Abstract : Li3 BO3 co-melts with Li6.4 La3 Zr1.4 Ta0.6 O12 to produce an amorphous boracic phase that consolidate the grain boundary, ultimately attaining garnet electrolyte with high Li + conductivity. Abstract : All solid-state batteries have received significant attention due to their excellent safety performance. As a key component, the garnet-type electrolyte is one of the best known electrolytes due to its air stability and good compatibility with metallic lithium. However, the total Li + conductivity of this kind of electrolyte is usually lower than that of the bulk electrolyte primarily due to the grain boundary resistance. In this study, we focused on engineering the electrolyte Li6.4 La3 Zr1.4 Ta0.6 O12 (LLZTO) by introducing Li3 BO3 (LBO) into it to form the electrolyte LLZTO/LBO with the aim to consolidate the grain boundary. Via characterization by both neutron and X-ray diffraction, the as-prepared LLZTO was indexed as a pure cubic phase, where Ta certainly substituted the Zr sites. LLZTO/LBO still maintained the cubic structure, and the B atoms did not occupy any cation sites in the unit cell. It was demonstrated that an amorphous phase of a boracic substance was trapped inside the cubic LLZTO phase. The amorphous boracic phase sutured the gaps among the LLZTO grains and then lowered the grain boundary resistance without introducing impurities, ultimately consolidating the solid-state electrolyte. Electrochemical impedance spectroscopy revealed that the total Li + conductivity of LLZTO/LBO reached 5.47 × 10 −4 S cm −1, much higher than those of the as-prepared Li7 La3 Zr2 O12 (LLZO) and LLZTO. Using LLZTO/LBO as an electrolyte, the LiNi0.8 Co0.1 Mn0.1 O2 /LiFePO4 hybrid solid battery showed an excellent cycling performance with the reversible capacity of 147.8 mA h g −1 at 0.2C for 100 cycles and the capacity retention of 93.8%. These results suggest that the consolidation of the grain boundary with LBO is a promising way to achieve an improved electrolyte, LLZO, with higher total Li + conductivity.